2018
DOI: 10.1007/s12035-018-1120-y
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A1-Dopamine D1 Receptor Heteromers Control the Excitability of the Spinal Motoneuron

Abstract: While the role of the ascending dopaminergic system in brain function and dysfunction has been a subject of extensive research, the role of the descending dopaminergic system in spinal cord function and dysfunction is just beginning to be understood. Adenosine plays a key role in the inhibitory control of the ascending dopaminergic system, largely dependent on functional complexes of specific subtypes of adenosine and dopamine receptors. Combining a selective destabilizing peptide strategy with a proximity lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 70 publications
0
31
0
Order By: Relevance
“…More generally, these results indicate that to inhibit a Gs-coupled receptor-mediated AC activation, the ligands need to simultaneously interact with heterotetramers of the corresponding Gs-coupled and Gi-coupled receptors. This has been so far shown for the A2AR-D2R [7], the A1R-D1R [48], the D1R-D3R [49], and now the A2AR-CB1R heterotetramers, where destabilization of their heteromeric interface leads to the disruption of the canonical Gs-Gi antagonistic interaction at the AC level without disruption of the Gi-coupled receptor-mediated inhibition of forskolin-induced AC activation.…”
Section: Discussionmentioning
confidence: 64%
“…More generally, these results indicate that to inhibit a Gs-coupled receptor-mediated AC activation, the ligands need to simultaneously interact with heterotetramers of the corresponding Gs-coupled and Gi-coupled receptors. This has been so far shown for the A2AR-D2R [7], the A1R-D1R [48], the D1R-D3R [49], and now the A2AR-CB1R heterotetramers, where destabilization of their heteromeric interface leads to the disruption of the canonical Gs-Gi antagonistic interaction at the AC level without disruption of the Gi-coupled receptor-mediated inhibition of forskolin-induced AC activation.…”
Section: Discussionmentioning
confidence: 64%
“…Adenosine acts at A1 receptors to inhibit interneurons within the CPG, which in turn affects the frequency of motor output. Previous research has focussed on the astrocyte-to-neuron communication mechanisms that may impact motor circuits (Witts et al, 2012(Witts et al, , 2015Miles, 2015, 2017;Acevedo et al, 2016;Acton et al, 2018;Rivera-Oliver et al, 2018). In this study, we have identified previously unexplored neuron-to-astrocyte signaling mechanisms which may drive astrocyte-dependent modulation of the spinal cord locomotor CPG.…”
Section: Discussionmentioning
confidence: 92%
“…There is converging evidence that stimulating astrocytes pharmacologically, or ablating astrocytes with gliotoxins, reveals purinergic-dependent, glial-derived modulation of the spinal cord locomotor CPG (Dale and Gilday, 1996;Dale, 1998;Brown and Dale, 2000;Witts et al, 2012Witts et al, , 2015Acton and Miles, 2015;Acevedo et al, 2016;Acton and Miles, 2017;Acton et al, 2018;Rivera-Oliver et al, 2018). Although astrocytes in other CNS regions demonstrate the ability to utilize other transmitters, such as glutamate or GABA (Malarkey and Parpura, 2008;Christensen et al, 2018); there is a paucity of evidence to suggest that other gliotransmitters are involved in the astrocytic control of the locomotor CPG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, changes to A 1 R and A 2A R expression following exercise could have a particularly potent influence on striatal function through its modulation of dopaminergic activity. Indeed, A 1 Rs and A 2A Rs form heteromeric complexes with dopamine 1 (D 1 R) with dopamine 2 (D 2 R) receptors, respectively [24,[36][37][38][39][40]. Agonist binding at A 1 Rs and A 2A Rs results in conformational changes to dopamine receptors and decreases dopamine receptor coupling to G-proteins, thereby reducing the effectiveness of dopaminergic signaling within the striatum [39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%